Fibre Optic Sensors with Nano-Structured Coatings. - James, Stephen W.; Tatam, Ralph P. (Institute of Physics (IOP), 2006)
A review of optical fibre devices employing nano-structured coatings is presented. Active and passive coatings, deposited using the LangmuirÃ¢Â Â Blodgett and electro-static self-assembly techniques, have been utilised to influence the transmission spectrum of optical fibres, with the aim of developing sensor elements and in-line components for telecommunications systems. Coupled waveguide, fibre grating and miniature FabryÃ¢Â Â Perot cavities are descri
Keywords: optical fibre; Langmuir–Blodgett; electrostatic self-assembly; second harmonic generation; chemical sensor; polished; long period grating; Fabry Perot interferometer